المساهمة في دراسة ديمومة خرسانة رمل المحاجر في منطقة وادي سوف تحت تأثير المياه الصاعدة. - جمال, زايد; إبراهيم, نقية; كمال, العايش (University of El-Oued, 2020)
"تعاني الواحات الجزائریة من قلة الرمال الصالحة للبناء, في حین نسجل تكدس الرمال الناتجة عن كسر الحصى تسمى ھذه الرمال عموما برمال المحاجر . في ھذا الصدد قامت عدة أبحاث تـُعنى بدراسة الخرسانة المعدة برمل المحاجر وقد تم إنشاء العدید من المشاریع بھذا النوع من الخرسانة. من جھة أخرى تعاني بعض مناطق الواحات الجزائریة من ظاھرة صعود المیاه التي تؤثر على المنشات والمباني في ھذه الدراسة حاولنا الإجابة عن إمكانیة استعمال خرسانة رمل المحاجر في منطقة وادي سوف المعرضة لصعود المیاه وما مدى دیمومة ھذا النوع من الخرسانة . الكلمات المفتاحیة" "The Algerian oases suffer from a lack of sand suitable for building, while we record the accumulation of sand resulting from breaking gravel. These sand are generally called sand quarries. In this regard, many researches have been carried out to study the concrete prepared with quarry sand, and many projects have been conducted with this type of concrete. On the other hand, some areas of the Algerian oases suffer from the phenomenon of the rise of water level, which affects infrastructure and buildings. In this study, we tried to see the possibility of using the concrete of quarry sand in Oued Souf region, which is subject to water rising level, and how long is this type of concrete sustainable."
Matéreaux en génie civil مذكرة ماستر تخصص
Keywords: رمل المحاجر ، الدیمومة، مقاومة الضغط ، مقاومة الشد عن طریق الانحناء ، فقد الكتلة; Quarry sand - Consistency - Pressure resistance - Tensile strength by bending - Mass loss